(untitled) - Moran, Michael J. (New York, 1992)
Contents: Atomic or molecular weights and critical properties of some common elements and compounds; Properties of saturated water (Liquid - vapor) Temperature table; Ideal gas properties of air...
Keywords: Thermodynamics,Nhiệt động học